Intercropping Growth Response of Edamame Plants on Oil Palm Land with the Application of Biosaka - Gunawan, Hari; Isra, Marzuti; Maisarah, Maisarah; Purjianto, Purjianto; Febrianto, Eka Bobby (Journal of Agriculture, 2025)
Oil palm is an essential commodity in Indonesia with excellent development potential, but the long waiting time required to produce oil palm plantations is a problem. Combining with multi-purpose tree species (MPTS) plants can solve this problem. Maximizing resources efficiently and environmentally friendly, the concept of plant intercropping entrepreneurship can be used with Edamame. The intercropping of edamame plants on oil palm plants must be carried out optimally to produce good-quality fruit. So, this study was conducted on the growth response of intercropping edamame plants on oil palm plantations with the provision of biosaka. This study aimed to determine the effect of biosaka and NPK fertilizer on the growth and yield of edamame plants. Based on the research that has been done, Biosaka has the potential to increase the productivity of edamame plants. The best dose for edamame plant production is in the P3B1 treatment (NPK 30gr/polybag + 20 ml/L/Polybag) as much as 100.97 g/plant, which can increase the weight of pods/plant, pod weight, and number of pods/plant. The fastest flower emergence age is in the B3 treatment, which is 40.55 days. The study results showed that the interaction between Biosaka and NPK fertilizer had no significant effect on the variable of plant height. The use of Biosaka on edamame plant variables that are not much different from the use of NPK fertilizer can be considered.